Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Complete the steps in the proof that show quadrilateral KITE with vertices [tex]\(K (0,-2), I (1,2), T (7,5), E(x,y)\)[/tex].

Using the distance formula:
[tex]\[ KI = \sqrt{(2 - (-2))^2 + (1 - 0)^2} = \sqrt{17} \][/tex]
[tex]\[ KE = \square \][/tex]
[tex]\[ IT = \square \][/tex]
[tex]\[ TE = \square \][/tex]

Therefore, KITE is a kite because [tex]\(\square\)[/tex].

Select the correct answers from each drop-down menu.


Sagot :

To solve this problem step-by-step, we'll first calculate the lengths of the sides of the quadrilateral KITE.

We'll use the distance formula:
[tex]\[ \text{Distance} = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]

Given the vertices of quadrilateral KITE:
- [tex]\( K(0, -2) \)[/tex]
- [tex]\( I(1, 2) \)[/tex]
- [tex]\( T(7, 5) \)[/tex]
- [tex]\( E(6, -1) \)[/tex]

Let's calculate the lengths of the sides one by one:

1. Calculate [tex]\( KI \)[/tex]
[tex]\[ KI = \sqrt{(1 - 0)^2 + (2 - (-2))^2} = \sqrt{1^2 + 4^2} = \sqrt{1 + 16} = \sqrt{17} \approx 4.123 \][/tex]

2. Calculate [tex]\( KE \)[/tex]
[tex]\[ KE = \sqrt{(6 - 0)^2 + (-1 - (-2))^2} = \sqrt{6^2 + 1^2} = \sqrt{36 + 1} = \sqrt{37} \approx 6.083 \][/tex]

3. Calculate [tex]\( IT \)[/tex]
[tex]\[ IT = \sqrt{(7 - 1)^2 + (5 - 2)^2} = \sqrt{6^2 + 3^2} = \sqrt{36 + 9} = \sqrt{45} \approx 6.708 \][/tex]

4. Calculate [tex]\( TE \)[/tex]
[tex]\[ TE = \sqrt{(6 - 7)^2 + (-1 - 5))^2} = \sqrt{(-1)^2 + (-6)^2} = \sqrt{1 + 36} = \sqrt{37} \approx 6.083 \][/tex]

So after calculating each side, let's fill in the drop-down values:

[tex]\[ K E = \sqrt{37} \][/tex]
[tex]\[ I T = \sqrt{45} \][/tex]
[tex]\[ T E = \sqrt{37} \][/tex]

Finally, KITE is indeed a kite because the lengths corresponding to [tex]\( KE \)[/tex] and [tex]\( TE \)[/tex] are equal:
[tex]\[ KE = TE = \sqrt{37} \][/tex]

A kite in geometry is defined as having two distinct pairs of adjacent sides that are equal in length.

Therefore, our final filled proof is:

Using the distance formula,
[tex]\[ K I = \sqrt{(2 - (-2))^2 + (1 - 0)^2} = \sqrt{17} \][/tex]
[tex]\[ K E = \sqrt{37} \][/tex]
[tex]\[ I T = \sqrt{45} \][/tex]
[tex]\[ T E = \sqrt{37} \][/tex]

Therefore, KITE is a kite because [tex]\( KE = TE \)[/tex].